2011
DOI: 10.1097/brs.0b013e31821945a3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Expression of mRNA for Interleukin-8 and Effects of Interleukin-8 Receptor Inhibitor in the Spinal Dorsal Horn in a Rat Model of Lumbar Disc Herniation

Abstract: IL-8 might be a potential therapeutic target in chronic radicular neuropathic pain because of disc herniation, CXCL8 inhibitor could be one of its promising therapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 63 publications
2
32
0
Order By: Relevance
“…Among the chemokines family, IL-8 and its receptors CXCR1/2 have been emerging as one of the most promising target for the pharmacological management of CIPN due to its implication in sympathetic components of inflammatory hypernociception and in neuropathic nociceptive response [4647]. Interestingly, a recent controlled clinical study showed a significant upregulation of IL8 gene expression in the skin biopsies of patients affected by CIPN [23].…”
Section: Discussionmentioning
confidence: 99%
“…Among the chemokines family, IL-8 and its receptors CXCR1/2 have been emerging as one of the most promising target for the pharmacological management of CIPN due to its implication in sympathetic components of inflammatory hypernociception and in neuropathic nociceptive response [4647]. Interestingly, a recent controlled clinical study showed a significant upregulation of IL8 gene expression in the skin biopsies of patients affected by CIPN [23].…”
Section: Discussionmentioning
confidence: 99%
“…20 In the study reported here, immunohistochemical examination of the spinal cord for GFAP, OX-42, and pERK at Day 41 after PRF administration revealed reactive astrocytes with thickened processes in the dorsal horn, ipsilateral and contralateral to disc herniation in the NP+sham-stimulation group; this astrocyte activation was not affected by PRF administration. In contrast, the numbers of microglia increased in the dorsal horn ipsilateral to disc herniation in the NP+sham-stimulation group (mean gray value 29 …”
Section: Microglia Astrocytes and Perkmentioning
confidence: 91%
“…In experimental studies, autologous nucleus pulposus (NP) implantation in the dorsal root ganglion (DRG) is used to initiate LDH in rats. Recent studies have reported that several chemokines were involved in the NP-induced neuropathic pain [5][6] . For example, it has been reported that IL-8 mRNA expression was increased in the DRG after NP exposure while IL-8 inhibition could attenuated NP-induced allodynia in the spinal cord 6 .…”
Section: ■ Introductionmentioning
confidence: 99%